Decarbonising end-use sectors : practical insights on green hydrogen (International Renewable Energy Agency, 2021)
The IRENA Coalition for Action brings together leading renewable energy players from around the world with the common goal of advancing the uptake of renewable energy. The Coalition facilitates global dialogue between public and private sectors to develop actions that increase the share of renewables in the global energy mix and accelerate energy transitions. Green hydrogen - hydrogen produced from renewable energy - can provide the critical link between renewable electricity generation and hard-to-abate sectors such as industry and heavy transport. Featuring several case studies on pioneering green hydrogen projects and first-hand interviews, this white paper by the Coalition provides insights from a renewable energy industry perspective on the growth opportunities of green hydrogen and what is needed from policy makers to accelerate its adoption worldwide.